Breaking the geometric magnetic frustration in controlled off-stoichiometric LuMn1+zO3+delta compounds - Figueiras, F. G.
This study explores controlled off-stoichiometric LuMn1+zO3+delta (vertical bar z vertical bar < 0.1) compounds, intended to retain the utter LuMnO3 intrinsic hexagonal symmetry and ferroelectric properties. X-ray powder diffraction measurements evidenced a single phase P6(3)cm structure. Thermo-gravimetric experiments show a narrow impact of oxygen vacancies while a distinguishable gas exchange at similar to 700 K, a surprisingly lower temperature when compared to perovskite systems. A comparison of different nominal ceramics revealed pertinent structural and magnetic property variations owing to subtle self-doping effects. Deviations from the archetypal antiferromagnetic state were detected below similar to 90 K suggesting local rearrangements of the nominal Mn3+ ions matrix, breaking the ideal geometrical spin frustration, leading to a non-compensated magnetic structure.